Post-enucleation retinoblastoma: Outcome analysis and evaluation of prognostic features - Amani Al-Kofide; Hind M Alkatan; Yasser Khafaga; Khawar Siddiqui; Rafat Jafri; Mouhab Ayas; Saleh A AlMesfer (Journal of Nature and Science of Medicine, 2021)
Background: The aim is to assess if International Classification for Retinoblastoma (ICRB) and American Joint Committee on Cancer Staging System (AJCC) for patients with advanced Retinoblastoma (RB) who underwent enucleation correlated in predicting the successful outcome of chemotherapy. Materials and Methods: Medical records of fifty-eight pediatric patients (age ≤14 years) who underwent enucleation at King Khalid Eye Specialist Hospital, and treated post enucleation at KFSH and RC from 2012 to 2016 were reviewed. Results: RB was unilateral in 30 (51.7%), bilateral in 26 (44.8%) and trilateral in 2 (3.4%). One (1.7%) had metastatic disease. Sixty-one enucleation was performed on 58 patients; unilateral in 55 (94.8%) and bilateral in the 3 (5.2%) cases. Disease was ICRB Group E in 43 (70.5%), Group D in 11 (18.0%), Group C and A in 3 (4.9%) each, and Group B in 1 (1.6%) at diagnosis (P < 0.001). The median age at diagnosis was the highest in Group E compared to other groups (P = 0.254). All patients received chemotherapy. Nine (18.8%) patients classified as Group D or E as per the ICRB classification turned out to be pT1 or pT2a (low-risk), while one classified as Group C was of stage pT1. Probability of 5-year overall survival for the whole cohort was 93.0% (±4.0%); 94.5% (±3.8%) for Group E (2 mortalities) and 80.0% (±17.9%) for Stage D with one event of mortality (P: 0.972). Conclusion: Older children presented with ICRB Group E. Group E eyes had a high pTNM risk group than Group D. ICRB tends to correlate with pTNM. The ICRB classification is essential for decision making on enucleation; however, AJCC pTNM classification plays a pivotal role in deciding on postenucleation adjuvant treatment.